Art and celebrity in the age of Reynolds and Siddons - McPherson, Heather (The Pennsylvania State University Press, 2017)
"Explores the vibrant visual and theatrical culture of eighteenth-century England. Focuses on the central role of images in the invention of modern celebrity culture"--Provided by publisher